SORTING IT OUT: REGULATION OF EXOSOME LOADING - Villarroya-Beltri, Carolina (Semin Cancer Biol, 2014)
Extracellular vesicles (EVs), a term that includes both exosomes of endocytic origin and vesicles derived from plasma membranes, are continuously secreted by cells to the extracellular environment, and represent a novel vehicle for cell-cell communication. Exosomes contain specific repertoires of proteins and RNAs, indicating the existence of mechanisms that control the sorting of molecules into them. Although the molecular mechanisms that regulate the loading of proteins into exosomes have been studied for years, the sorting of RNA has been elusive until recently. Here we review the molecular mechanisms that control the sorting of molecules into exosomes, with special attention to the sorting of RNA. We also discuss how the cellular context affects the composition of exosomes, and thus the outcome of the communication between the exosome-producer and recipient cells, with particular focus on the communication between tumor cells and with cells of the tumor microenvironment.